2015
DOI: 10.48550/arxiv.1511.06392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Random-Access Machines

Abstract: In this paper, we propose and investigate a new neural network architecture called Neural Random Access Machine. It can manipulate and dereference pointers to an external variable-size random-access memory. The model is trained from pure input-output examples using backpropagation.We evaluate the new model on a number of simple algorithmic tasks whose solutions require pointer manipulation and dereferencing. Our results show that the proposed model can learn to solve algorithmic tasks of such type and is capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Neural Algorithm Execution. Many works have studied neural execution in different domains before (Zaremba & Sutskever, 2014;Kaiser & Sutskever, 2015;Kurach et al, 2015;Reed & De Freitas, 2015;Santoro et al, 2018;Yan et al, 2020). With the rapid development of GNNs in graph representation learning, learning graph algorithms with GNNs has attracted researchers' attention (Veličković et al, 2019;Xhonneux et al, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Neural Algorithm Execution. Many works have studied neural execution in different domains before (Zaremba & Sutskever, 2014;Kaiser & Sutskever, 2015;Kurach et al, 2015;Reed & De Freitas, 2015;Santoro et al, 2018;Yan et al, 2020). With the rapid development of GNNs in graph representation learning, learning graph algorithms with GNNs has attracted researchers' attention (Veličković et al, 2019;Xhonneux et al, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…A number of methods augment the short-and long-term memory internal to recurrent networks with external "working" memory, in order to realize differentiable programming architectures that can learn to model and execute various programs , Sukhbaatar et al, 2015, Joulin and Mikolov, 2015, Reed and de Freitas, 2015, Grefenstette et al, 2015, Kurach et al, 2015. Unlike our approach, these methods explicitly decouple memory from computation, mimicking a standard computer architecture.…”
Section: Related Workmentioning
confidence: 99%
“…A central challenge of non-convex optimization is avoiding sub-optimal local minima. Although it has been shown that the variable can sometimes converges to a neighborhood of the global minimum by adding noise [16,17,18,19,20], the convergence rate is still a problem. Note that the DP method has some probability to escape "appropriately shallow" local minima because the moving direction of the variable is generated by solving several sub-problems instead of the original problem.…”
Section: Related Workmentioning
confidence: 99%